Regional Specialization and Labor Productivity of Food Industry in South Sumatra - Melliny, Vinny Dwi; Gustriani, Gustriani; Zainal, Imelda; Pertiwi, Rasyida (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
SMEs became the leading sector contribute to Gross Domestic Product (GDP) in Indonesia. The role of SMEs not only can give positive impact encourage potential development sectors. This paper is to investigate the relationship between the characteristics of regional specialization and labor productivity of small enterprises in the Food industry using the regency or city level data of South Sumatra from 2008-2018. The study used secondary data from the Department of Trade and Industry of South Sumatra for 17 regencies/cities in South Sumatra. Our study proceeds in two steps. First, we used Location Quotient (LQ) to identify the regional specialization. Second, we measured the impact of regional specialization on labor productivity including other regional variables; investment, a total of enterprises, size of employment, Gross Domestic Product Regional (GRDP), and Gross Enrolment Rate based on the panel data of regencies or cities. In the first step, we found that eight regencies specialized in the Food industry. Those typically concentrated near of big city where few enterprises dominate. Next, the LQ, investment, average size of employment, GRDP, and a total of enterprises have a significant effect on labor productivity while the education variable does not influence regional economic growth.  According to this result, it should be cautioned that agglomeration may cause undesirable competition for raw materials leading to a detrimental result. This strongly suggests that to fully achieve labor productivity in South Sumatra, there is a need for the implementation of appropriate policy measure to overcome this issue.